IDENTIFIKASI TUMBUHAN SUMBER PANGAN DI HUTAN TEMBAWANG DESA AUR SAMPUK KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Sumarlin, Donni; Dirhamsyah, M.; Ardian, Hafiz (JURNAL HUTAN LESTARI, 2016)
This research aimed to determine the types of plants food sources available and used by communities in Tembawang forest Sengah Tumila subdistrict Landak. The benefits of this research can provide information about food sources and utilization of plant communities that exist around the village of Aur Sampuk, as well as the basis for management and development of the region by the agencies involved in the protection, conservation and utilization of plant food resources in the future. This study used snowball sampling technique or performed in sequance by asking for information on people who had bean interviewed prior to interview, observatian, and literature study. Based on the results of the study found as many as 50 plants classified to 35 families. Most number of them were arecaceae and moraceae. Every family had 6 species. Part used are part of the fruit that as much as 43 species. Where 33 of 50 kinds of the pland can be consumed directly methods with cooked 17 species, the most widely used is derived from the group of fruits that 43 species, vegetables 35 species, as musch as 20 species is a wild plant Keywords : Identification food pland, tembawang forest